(untitled) (Journal of the College of Basic Education, 2022)
The importance of the research lies in the fact that it will diagnose a number of problems and obstacles facing the physical education lesson and the use of modern strategies to come up with a number of conclusions and recommendations that will contribute to addressing these obstacles and problems and work on developing the physical education lesson. These lessons. The researcher used the experimental method, and the research sample consisted of middle school students, and the number of its members was (50) students. The results were presented and discussed in the fourth chapter, where the findings of the two researchers were discussed